Education for integration: four pedagogical principles. Issue 6 (21st December 2015) - Cook, Ailsa; Harries, John; Huby, Guro
Abstract : Purpose: – The purpose of this paper is to consider how postgraduate education can contribute to the effective integration of health and social care through supporting public service managers to develop the skills required for collaborative working. Design/methodology/approach: – Review of documentation from ten years of delivery of a part-time postgraduate programme for health and social care managers, critical reflection on the findings in light of relevant literature. Findings: – The health and social care managers participating in this postgraduate programme report working across complex, shifting and hidden boundaries. Effective education for integration should: ground learning in experience; develop a shared language; be inter-professional and co-produced; and support skill development. Originality/value: – This paper addresses a gap in the literature relating to the educational and development needs of health and social care managers leading collaborative working.